Exploring nirmatrelvir derivatives through P2 substituent modifications and warhead innovations targeting the main protease of SARS-CoV-2 - Martins, Felipe Cardoso Prado; Lang, Johannes; Rocho, Fernanda dos Reis; Wang, Xianxian; Bonatto, Vinícius; Lameira, Jerônimo; Klein, Christian D.; Montanari, Carlos Alberto (Archiv der Pharmazie, 2025)
The COVID-19 pandemic underscored the urgent need for effective antiviral agents, particularly against coronaviruses, which pose a continuing threat of future outbreaks. Targeting the main protease (Mpro), a key enzyme in viral replication, represents a promising therapeutic strategy. This study investigates structural modifications to known Mpro inhibitors, focusing on substitutions at the P2 position to explore alterations in both inhibitory potency and metabolic stability. Computational modeling and biochemical assays revealed that incorporating large, hydrophobic, and π-rich groups, such as the 4-phenylproline, significantly enhances binding affinity. Additionally, we evaluated warheads that have not yet been explored in the context of SARS-CoV-2 Mpro inhibition. Among these, fluoro-vinylsulfone and nitrile groups demonstrated superior inhibitory activity. A fragment-merging strategy combining an optimized P2 substituent with the nitrile warhead yielded a hybrid molecule with binding affinity comparable to nirmatrelvir. However, other analogs incorporating individual warhead optimizations displayed similar potency. These findings generate valuable insights into the design of robust Mpro inhibitors and support their potential development as broad-spectrum antiviral agents.
Online veröffentlicht: 29. November 2025
Gesehen am 24.02.2026